Telerreality and world consumption (Signos do Consumo, 2021)
This investigation, based on the perception of television as a mediator of the external world that produces other reality effects, aims to understand and problematize the interference of telereality in the construction of possible television worlds, in an attempt to attract the viewer/consumer. For such purpose, it discusses the televisual text regarding its text model and the other texts that it establishes links, focusing on the discursive strategies used by television that offer four distinct realities to consumption.